Crystal structure of catena-poly[bis(µ2-3,5-bis(1-imidazolyl)pyridine-κ2 N:N′)-(µ2-3-nitrophthalato-k3 O,O′:O″)cadmium(II)] dihydrate, C30H25N11O8Cd - Yin Wei-Dong; Liu Qian-Long; Zhao Ya-Jing; Gong Xiao-Ru; Li Gui-Lian (Zeitschrift für Kristallographie - New Crystal Structures)
C30H25N11O8Cd, orthorhombic, Pnma (no. 62), a = 17.9344(3) Å, b = 18.2722(3) Å, c = 9.5619(2) Å, V = 3133.44(10) Å3, Z = 4, R gt(F) = 0.0345, wR ref(F 2) = 0.0707, T = 293.28(10) K.